Diversity of Aquatic Beetles (Insecta: Coleoptera) of Navegaon National Park, Maharashtra, India - Deb , Rita; Subramanian, K. A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The present study was carried out during the year 2017 to gain knowledge on diversity of aquatic beetles from Navegaon National Park in Maharashtra. A total of 19 species belonging to 13 genera and 3 families of aquatic coleoptera were recorded. Family Dytiscidae was found to be species rich group followed by Hydrohilidae and Gyrinidae. Sixteen species were recorded for the first time from the national park.